2012
DOI: 10.2134/jeq2011.0166
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biochar Amendment on Tylosin Adsorption-Desorption and Transport in Two Different Soils

Abstract: The role of biochar as a soil amendment on the adsorption-desorption and transport of tylosin, a macrolide class of veterinary antibiotic, is little known. In this study, batch and column experiments were conducted to investigate the adsorption kinetics and transport of tylosin in forest and agricultural corn field soils amended with hardwood and softwood biochars. Tylosin adsorption was rapid at initial stages, followed by slow and continued adsorption. Amounts of adsorption increased as the biochar amendment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(18 citation statements)
references
References 29 publications
1
15
1
1
Order By: Relevance
“…Unlike some recent studies (Fan et al, 2011;Jeong et al, 2012), no tailings and asymmetrical breakthroughs were observed for the bromide BTCs, indicating the absence of physical non-equilibrium conditions during the transport of the antibiotics through the soil columns. The nonsorbing bromide breakthrough curves were all quite symmetrical (Fig.…”
Section: Transport Modellingcontrasting
confidence: 91%
See 1 more Smart Citation
“…Unlike some recent studies (Fan et al, 2011;Jeong et al, 2012), no tailings and asymmetrical breakthroughs were observed for the bromide BTCs, indicating the absence of physical non-equilibrium conditions during the transport of the antibiotics through the soil columns. The nonsorbing bromide breakthrough curves were all quite symmetrical (Fig.…”
Section: Transport Modellingcontrasting
confidence: 91%
“…where R (the dimensionless retardation factor) accounts for fully reversible reactions of a solute species in the soil system (Jeong et al, 2012), ρ is the soil bulk density (kg m −3 ), θ is volumetric water content (v/v), and K d , the linear sorption coefficient (L kg −1 ). However, for nonlinear sorption coefficients obtained from Freundlich isotherms the equation can be written as…”
Section: Transport Modellingmentioning
confidence: 99%
“…However, the study undertaken by Jeong et al [80] found that despite using biochar from different feedstock materials and different thermal treatment conditions for the removal of tylosin, the removal rate was in the range of 10% for all the products. This outcome is attributed to the chemical structure of tylosin which includes several hydroxyl groups when compared with other antibiotics such as sulfamethoxazole.…”
Section: Adsorption Using Biocharmentioning
confidence: 99%
“…Feedstocks of animal or human origin may also contain substantial quantities of unmetabolized antibiotics that could lead to the development of antibiotic resistance in the soil microflora on amendment (Ippolito et al, 2012). The fate of antibiotics on charring is largely unknown, even though active sorption of veterinary drugs by biochars has been demonstrated in soil (Jeong et al, 2012) and in water (Li et al, 2015).…”
Section: Resultsmentioning
confidence: 99%